Features of intra- and extra-cranial blood fl ow in patients with essential hypertension stage II according - V. V. Syvolap; E. A. Poznanskaya; R. P. Nikulina; А. V. Vizir (Zaporozhye State Medical University, 2014)
Abstract Today diseases of the cardiovascular system are called the problem number 1in the world, including Ukraine. Every year more than 500 thousand Ukrainians dye from CVDs, i.e. 1370 people on average dye every day. Smoking is one of the most serious threats to health, especially with regard to cardiovascular disease. Every year, smoking kills more than 1.2 million people in Europe (of which 450 thousand - due to cardiovascular diseases) and about 650 thousand people of the EU countries (including from cardiovascular problems - 185 thousand). Analysis of the literature suggests paucity and contradictory information about changes in the functional status of the various systems of the body while smoking. The aim of the work was to study the peculiarities of cerebral hemodynamics in patients with hypertension stage II depending on smoking status. Material and methods. We examined 100 patients with essential hypertension stage II low additional cardiovascular risk, 53 men and 47 women. Depending on the smoking status (at least 10 years), all patients were divided into 2 groups: a group of smokers included 30 patients, in the group of non-smokers there were 70 patients. To assess cerebral hemodynamic Doppler ultrasound and duplex scanning methods were used. Statistical processing of the material was performed using the software package Statistica 6.0 («Statsoft», USA, № license AXXR712D833214FAN5). Results and discussion. Analysis of the data shows the predominance of authentic vascular resistance index in the right CCA by 3.3% (p = 0.033), in the right MCA by 8.5% (p = 0.05), in the left MCA by 7.1% (p = 0.042) in hypertensive patients with smoking status, compared with non-smoking hypertensive patients. In smokers with hypertension statistically significant increasing of the indicator "reserve vasoconstriction" by 4.63 times (p = 0.029) in the left ICA and by 3.01 times (p = 0.031) in the right ICA was also found compared with data rates in nonsmokers hypertensive patients. The results of our studies in hypertensive patients revealed the following gender differences. Significant predominance of resistance index in the right ICA by 10.8%, the maximum linear velocity of blood flow in the left ICA by 22.0% was obtained in female smokers compared with male smokers. At the same time, in women-smokers lower values of systolic and diastolic index in the right CCA by 8.7% and resistance index in the left MCA by 4.9% than in male smokers were observed. Conclusions: Disorders of cerebral blood flow in hypertensive patients with smoking status compared with hypertensive nonsmokers were characterized by more pronounced carotid artery spasm. In hypertensive patients with smoking status most sensitive Doppler indicators of the great neck and head arteries are Pourcel resistance indices in the common carotid and middle cerebral arteries, as well as indicators of cerebrovascular reactivity in the internal carotid artery. Gender differences of Doppler indices of the great neck and head arteries in hypertensive patients with smoking status were characterized by: higher vascular resistance in the common and internal carotid arteries in women and in the middle cerebral arteries in men, possibly due to spasm of the arteries under the influence of tobacco smoke.